Reacción álcali- carbonato, perjudicial para el acero del hormigón armado, utilizando agregados pétreos de las minas, Cerro Negro y Rio Chambo - Velásquez Sevilla, Jordy Josué (2018)
Reinforced concrete is one of the most used materials in the construction industry, one of the reasons is due to the physical properties of the material: compression and traction, the concrete to work more than compression also fulfills the function of protecting the steel from corrosive agents from the outside or properly from the aggregates used. To identify in what percentage the stone aggregates of the Cerro Negro and Rio Chambo mines influence the corrosion of the steel, the accelerated corrosion test with electricity was carried out, the same one that consisted in elaborating 36 cubes of concrete distributed in half between the aggregates of the mine of Cerro Negro and Rio Chambo, with a steel bar embedded in the center, constant electricity was transferred to the steel bars for 500 hours. At the end of the essay, the steel bars that were embedded in the concrete cubes made with the aggregates of the Cerro Negro mine presented a higher percentage of corrosion compared to the steel bars embedded in the concrete cubes made with the aggregates of the Rio Chambo mine, the reason is for the salts that the aggregate of the Cerro Negro mine has. KEY WORDS: Corrosion, fine and coarse aggregates, Chimborazo IP cement, Holcim GU cement, accelerated corrosion test.